Fritz Hans Schweingruber, 1936-2020, who moved the boundaries of wood anatomy and dendrochronology - Čufar, Katarina (Les (Ljubljana), 2020)
Prof. Dr. Fritz Hans Schweingruber (29 February 1936 - 7 January 2020) was a key wood anatomist and dendrochronologist, teacher and organiser of summer field schools, who established an extensive network of scientists, wrote key books, contributed to the construction of publicly accessible databases, popularised and revealed unimaginable possibilities for the development and use of wood anatomy and dendrochronology. He established an intellectual legacy that will inspire his followers around the world for a long time to come.
Keywords: anatomija lesa; dendrochronology; dendrokronologija; poučevanje; teaching; wood anatomy